1986
DOI: 10.1577/1548-8659(1986)6<109:hvamro>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hook-and-Line Vulnerability and Multiple Recapture of Largemouth Bass under a Minimum Total-Length Limit of 457 mm

Abstract: Data from a catch‐and‐release largemouth bass (Micropterus salmoides) fishery at Ridge Lake, Illinois, in which the minimum size limit was 457 mm total length, were used to test the null hypothesis that the recapture of largemouth bass is a normally distributed random event. Comparison of recapture data with a Poisson distribution for randomly selected fish from the 1976 year class demonstrated that recapture was not a random phenomenon and implied that individual fish varied in their vulnerabilities. Low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…About 37% of the fish were caught more than once, and 21% were never captured. This and other studies on largemouth bass (Burkett et al 1986;Hackney and Linkous 1978) indicate that some individual fish may be more likely than others to be caught by hook-and-line methods. Other studies of rainbow trout (Dwyer and Piper 1984;Brauhn and Kincaid 1982;Moring 1982;Hudy and Berry 1983) indicate that vulnerability to angling may be heritable.…”
Section: Hook and Linesupporting
confidence: 55%
“…About 37% of the fish were caught more than once, and 21% were never captured. This and other studies on largemouth bass (Burkett et al 1986;Hackney and Linkous 1978) indicate that some individual fish may be more likely than others to be caught by hook-and-line methods. Other studies of rainbow trout (Dwyer and Piper 1984;Brauhn and Kincaid 1982;Moring 1982;Hudy and Berry 1983) indicate that vulnerability to angling may be heritable.…”
Section: Hook and Linesupporting
confidence: 55%
“…Burkett et al (1986) demonstrated variation in vulnerability to hook-and-line capture in a largemouth bass population and suggested that differences in vulnerability were heritable. One possible effect is a general loss of genetic diversity.…”
Section: Biological Effects Of Competitive Fishingmentioning
confidence: 99%
“…Based on recapture rates, Burkett et al (1986) concluded that largemouth bass populations contained stocks of high and low vulnerabilities. They estimated that only 15% of the population was vulnerable to capture, and those fish were caught on average about two times every season.…”
Section: Voluntary Release and Recapturementioning
confidence: 99%